2010
DOI: 10.15388/ekon.2010.0.976
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Cost of Equity in the Baltic Region

Abstract: During the last two decades the Baltic region has been subject to several episodes of investment volatility and political turmoil. Although financial liberalization processes undertaken in these countries could reduce the cost of equity, it seems that investors have been cautious in investing in the Baltic region. In this research, we estimate the cost of equity per industry sector in three Baltic countries (Estonia, Lithuania and Latvia) during the period [2005][2006][2007][2008] and conclude that the cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…Baltic countries had also historically exhibited high economic and political risk which was represented by the composite risk rating (CRR) high volatility figures (Erb, Harvey & Viskanta, 1996; Fuenzalida, Mongrut & Nash, 2005). Using ex-post cost of equity across all industry sectors in the Baltic countries, Mongrut, Paškevičius, Dubinskas, Kovalevskaja and Fuenzalida (2010) demonstrated that the cost of equity increased during the period 2005–2007, signalling that the Baltic country capital market was not conducive from a financing point of view. The Baltic countries experienced strong real GDP growth between the years 2000 and 2007 but post-2006–2007, the Baltics spiralled into recession (Martin, 2010).…”
Section: Business Landscape In Baltic Countriesmentioning
confidence: 99%
“…Baltic countries had also historically exhibited high economic and political risk which was represented by the composite risk rating (CRR) high volatility figures (Erb, Harvey & Viskanta, 1996; Fuenzalida, Mongrut & Nash, 2005). Using ex-post cost of equity across all industry sectors in the Baltic countries, Mongrut, Paškevičius, Dubinskas, Kovalevskaja and Fuenzalida (2010) demonstrated that the cost of equity increased during the period 2005–2007, signalling that the Baltic country capital market was not conducive from a financing point of view. The Baltic countries experienced strong real GDP growth between the years 2000 and 2007 but post-2006–2007, the Baltics spiralled into recession (Martin, 2010).…”
Section: Business Landscape In Baltic Countriesmentioning
confidence: 99%
“…Таким образом, проверка гипотезы о равенстве константы нулю по сути является проверкой, объясняющей силы модели САРМ. Единое мнение о равенстве константы нулю не достигнуто: например, Йошино с соавторами, а также Хасан с соавторами (Yoshino et al, 2009; 26 Hasan et al, 2011 27 ) получили результаты, отвергающие нулевую гипотезу, и приходят к выводу о несостоятельности локальной САРМ, в то время как Дивани и Михайлидис с соавторами (Diwani,2010; 28 Michailidis et al, 2006 29 ) подтверждают незначимость константы и ее соответствие нулевому значению.…”
Section: эмпирический анализ зависимости ожидаемой доходности на собсunclassified
“…Поэтому актуальным становится иное направление регрессионного анализа. Оно заключается в том, что выборка разбивается на два периода: базовый и контрольный (Mongrut et al, 2010). По базовому периоду с помощью регрессионного анализа оценивается коэффициент бета, после чего предсказанные значения доходности сравниваются с наблюдаемыми значениями доходности.…”
Section: тестирование моделей оценки затрат на собственный капитал наunclassified
See 1 more Smart Citation
“…The downside model generates a higher required return for emerging markets than for developed markets contradicting the conclusions of CAPM. Mongrut et al (2010) considered sample of 32 companies from the Baltic region for the period of 2000-2008. They showed that cost of equity forecasts obtained according to DCAPM are consistent with observations and adequately reflect the differences in the cost of equity for companies from different sectors.…”
Section: Literature Reviewmentioning
confidence: 99%